Ascendance by Descendants? On Intergenerational Education Mobility in Latin America - Daude, Christian (OECD Publishing, 2011)
This paper studies intergenerational social mobility in Latin America. We show that persistence in educational achievements across generations is high compared to other parts of the world. That is, not only is the income distribution in Latin America highly unequal, but profound differences in opportunities persist from one generation to the next. This persistence arises from a combination of factors: high returns to education, relatively low progressivity in public investment in human capital and lack of access to proper financing for poor and middle-income families. Education and other social policies to boost upward mobility in the region are discussed
Keywords: Development